Mucociliary transport in trachea of patients with cystic fibrosis. Issue 1 (January 1976) - Yeates, D B; Sturgess, J M; Kahn, S R; Levison, H; Aspin, N
Abstract : Mucociliary tracheal transport rates were measured in 20 patients with cystic fibrosis, in whom these rates ranged from 0 to 12.8 mm/min. The patients were divided into 3 roughly equal groups on the basis of their transport rates. (1) Those in whom no abnormality in mucociliary transport was detected in the trachea; (2) those in whom normal transport rates were measured but in whom abnormalities such as cessation, or reversal of bolus movement were observed; (3) those in whom no normal transport rates were observed. In the first group the rates were similar to those observed in a population of healthy adults. These normal rates were observed in some patients who had a productive cough. The mean mucociliary tracheal transport rate increased with increasing maximum midexpiratory flow. Those patients with a low Shwachman score and poor arterial oxygen tension tended to fall into groups 2 and 3. In the ciliary dyskinesia assay in rabbit trachea the serum from the patients with the higher transport rates tended to initiate more rapid discharge of material from the epithelium and ciliary dyskinesia.